'Sharing our voices'—Taking a learning disability history project online during a pandemic. (11th April 2022) - Reeve, Jacquelyn; Farmer, Emily; Bayley, William
Abstract: This paper reviews the challenges faced by a team at the Grace Eyre Foundation in running a coproduced oral history project during the pandemic. It examines the benefits and challenges of working online, comparing this to face‐to‐face approaches. For over 100 years, the Grace Eyre Foundation has provided support to people with learning disabilities and/or autism across Sussex. Its founder, Grace Eyre Woodhead, was a pioneer—from around 1896 until her death in 1936, she advocated supporting people with learning disabilities in the community rather than in large, isolated institutions. With Heritage Lottery funding awarded in 2019, 'Sharing Our Voices' set out to: create a digital, oral history collection of people who had lived in Shared Lives arrangements since the 1950s. create a digital archive of the life and work of Grace Eyre Woodhead. devise a play inspired by the experience of exploring these histories, to be performed as part of the Brighton Fringe Festival 2021. This article: Describes how the Project Team adapted to continue the project during the 2020–2021 lockdowns. Discusses the opportunities, and limitations, of training people using online technologies. Demonstrates the opportunities, and limitations, of conducting oral history interviews online. Concludes that while online technologies are useful, enabling oral history work to continue under restrictions, there are limits to what can be achieved. We set out some of our learning here but it is hard to see how working online could ever fully replace the benefits of meeting face to face. Accessible summary: This article tells the story of the 'Sharing Our Voices' learning disability history project. The project supported people with learning disabilities to explore their own history and tell their own stories. The article talks about how the project changed to cope with Lockdown so everyone was still able to take part and enjoy the experience. The history training and interviews were held over Zoom as we could not meet face to face. There were good and bad things about working online. This article talks about the problems people with learning disabilities had trying to use Zoom or the internet. It was good that we were able to do things despite the lockdown but some people couldn't get online. We talk about the reasons. Not being able to get on‐line affected people in all areas of their lives as they were not able to access activities and services online. They were isolated during lockdown. It's important that we talk about that and improve internet access for people with learning disabilities. We interviewed people about their history. We had to do that over Zoom at first, but later we were able to meet together in a socially distanced way. We learned a lot about interviewing people online. We include examples of what worked well and not so well. We think it's good to share what we learned so it can help future projects.